СONFLICTOLOGICAL COMPETENCE OF GRADUATES OF HIGHER EDUCATIONAL INSTITUTION - A. V. Agafonov (Научный вестник МГТУ ГА, 2016)
The article deals with value of discipline "Conflictology" for training university graduates, an increase of their conflictological competence. The analysis of a lecture and practical training in the course of which a certain knowledge, skills are formed is given. Four investigation phases individual conflictological characteristics of the personality are considered: personal, intra personal, interpersonal and intra group. The system of tests for definition of personal characteristics at each stage is offered and their role in designing individual conflictological characteristics of the personality is shown. A valid conclusion about influence of this characteristic on a choice of the correct style of behavior in various types of the conflicts is given.